Analysis on Microbial Profiles & Components of Bile in Patients with Recurrent CBD Stones after Endoscopic CBD Stone Removal: A Preliminary Study - Jung Wan Choe (Journal of Clinical Medicine, 2021)
Background/Aim: Common bile duct (CBD) stone recurrence after endoscopic treatment is a major concern as a late complication. Biliary bacterial factors and biochemical factors determine the path of gallstone formation. The aim of this preliminary study was to investigate the microbial profile and components of bile in patients with and without recurrent CBD stones after endoscopic CBD stone removal. Methods: Among patients who had undergone an initial endoscopic procedure for the removal of CBD stones and were followed up for >2 years, 11 patients who experienced at least two CBD stone recurrences, six months after endoscopic retrograde cholangiopancreatography (ERCP), were categorized into the recurrence group. Nine patients without CBD recurrence events were matched. Results: Polymicrobial infections are generally seen in all patients who have biliary sphincteroplasty. Microbial richness, measured by the numbers of operational taxonomic units (OTUs), was reduced in the recurrence group. The microbial evenness was also significantly lower than in the non-recurrence group. The overall microbial communities in the recurrence group deviated from the non-recurrence group. Infection with bacteria exhibiting β-glucuronidase activity was more frequent in the recurrence group, but there was no statistical significance. In an analysis of the bile components, the bile acid concentration was higher in the non-recurrence group than in the recurrence group. However, the other metabolites were not significantly different. Conclusions: Microbiota dysbiosis and altered bacterial community assembly in bile duct and decreased bile acid in bile juice were associated with recurrence of bile duct stone.